The Efforts to Increase the Purchasing Decision of Skechers Shoes at After-Disc Shoe Shop - Muslikhun, Alfin; Sulistijanti, Wellie (Review of Management and Entrepreneurship, 2024)
This research aims to test how much influence factors have in increasing consumers' decisions to buy original shoes at the After-Disc Shoe Shop. The population in the research is all customers who buy Skechers shoes at the After store with unlimited consumers. The research sample consisted of 100 people who were calculated using the Lames haw formula, and the sampling method used the Accidental Sampling method. The data was processed using the SPSS version 22 application. The test results show that price plays a significant positive role in purchasing decisions. Additionally, store image has been proven to have a significant positive role in buying decisions. Product quality also plays a significant positive role in influencing purchasing decisions. The coefficient of determination value is 73.7%, which means that purchasing decisions in this study are influenced by price variables, store image, and product quality. The remaining 26.3% is the influence of other variables. Simultaneous testing produces price, store image, and product quality, which together play a role in purchasing decisions.